2001
DOI: 10.1016/s0006-3495(01)76153-x
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Induced Nonconductive Pre-Pores and Metastable Single Pores in Unmodified Planar Lipid Bilayer

Abstract: Electric fields promote pore formation in both biological and model membranes. We clamped unmodified planar bilayers at 150-550 mV to monitor transient single pores for a long period of time. We observed fast transitions between different conductance levels reflecting opening and closing of metastable lipid pores. Although mean lifetime of the pores was 3 +/- 0.8 ms (250 mV), some pores remained open for up to approximately 1 s. The mean amplitude of conductance fluctuations (approximately 500 pS) was independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
192
2
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(229 citation statements)
references
References 36 publications
14
192
2
1
Order By: Relevance
“…Increasing the applied potential difference is predicted to lower and broaden the local energy minimum that supports the hydrophilic pore, and lower the barrier to unbounded pore expansion. electrical recording (5,22,23); however, here, by isolating individual oSCR signals, we are able to extend observation of these phenomena to higher potentials, where the individual signals would be obscured in a purely electrical measurement. We have observed that all of these modes can occur at elevated potentials, with no apparent favor of one mode over another.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Increasing the applied potential difference is predicted to lower and broaden the local energy minimum that supports the hydrophilic pore, and lower the barrier to unbounded pore expansion. electrical recording (5,22,23); however, here, by isolating individual oSCR signals, we are able to extend observation of these phenomena to higher potentials, where the individual signals would be obscured in a purely electrical measurement. We have observed that all of these modes can occur at elevated potentials, with no apparent favor of one mode over another.…”
Section: Resultsmentioning
confidence: 94%
“…The transient nature and small size of electropores place significant limitations on the measurement of electropore dynamics, and more fundamentally on their direct detection. Electrical single-channel recording (SCR) can resolve these dynamics at high time resolution (22,23); however, SCR is limited in that it can only detect the total current across the membrane, and is thus unable to resolve whether conductance events are due to single or multiple permeabilization events. Indeed, the most common characteristic for electroporation in SCR would be a "noisy" trace that precedes bilayer rupture (see Fig.…”
Section: Previous Imaging Of Electroporesmentioning
confidence: 99%
“…Since there are no constant, unitary conductance steps in these recordings, they do not resemble recordings from typical ionic channels where the conduit from one side of the membrane to the other is exclusively lined by protein. Instead, these results reveal striking similarities to lipidic pores, in which the pore is lined by lipid headgroups (9,10).…”
mentioning
confidence: 83%
“…Membrane tubules were made by patch-clamping a planar phospholipid bilayer membrane formed on a Teflon orifice (30). A fire-polished glass pipette was pressed against the planar BLM Abbreviations: BLM, bilayer lipid membrane; DPhPC, diphytanoyl phosphatidylcholine; DNPC, dinervonoyl phosphatidylcholine; OPC, oleoyl phosphatidylcholine; OPE, oleoyl phosphatidylethanolamine; Chol, cholesterol; cP, centipoise; NT, narrow tubule; WT, wide tubule.…”
Section: Methodsmentioning
confidence: 99%